Improving Student Learning Outcomes through Implementation Diorama Media Based on Problem Based Learning - Choiroh, Luluk Zazilatul; Renaningtyas, Peni Catur; Sudarti, Sudarti; Wuryaningrum, Rusdhianti (EDUCARE: Journal of Primary Education Published by Faculty of Tarbiyah and Teacher Training, Kiai Haji Achmad Siddiq State Islamic University of Jember, East Java, Indonesia, 2024)
This study examines the effectiveness of Problem-Based Learning (PBL)-based diorama media in improving student learning outcomes on the material of ASEAN agricultural products in grade VI of SDN Pasrujambe 08. The method used is Classroom Action Research (CAR), which is implemented in two cycles, each consisting of planning, action implementation, observation, and reflection. Data were obtained through learning outcome tests, observation, and documentation. The results of the study showed a significant increase in student learning outcomes. Classical completeness increased from 40% in the pre-cycle to 60% in cycle I and finally reached 80% in cycle II, meeting the established classical completeness standards. Applying PBL-based dioramas has proven effective in helping students understand the types of ASEAN agricultural products while developing critical thinking, problem-solving, and collaborative skills. In addition, this method increases students' active involvement in the learning process, making the learning experience more interactive and contextual. This study contributes to the educational literature by offering innovative learning strategies that teachers can apply to create a more interesting learning atmosphere. These results can also be a reference for developing a PBL-based curriculum at the elementary school level to improve the quality of learning.